Implementasi Alexa Voice Command Untuk Pembacaan Informasi Sensor Pada Rumah Pintar - Romario Siregar; Sabriansyah Rizqika Akbar; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Rapid technological development is needed in facilitating access to technology at this time. Because of the increasing mobility of the people, the higher the level of neglect of small things such as forgetting to turn off electronic equipment such as lights, televisions, air conditioners, and others. Smart home (Smart Home), one of the solutions that can be offered to overcome this problem. Smart Home is a term used for homes that have electronic equipment or security systems that are integrated with each other and can be monitored for use. The developing method in monitoring smart homes is to use sound (Speech Recognition). One of the Amazon voice services that can be used is Alexa Voice Service. In this study, Alexa Voice Service will be implemented to the Raspberry Pi which functions as the speech recognition module and Raspberry Pi can receive sensor data that contains the value of air quality, temperature, and smoke wirelessly which will then be sent to the Alexa Skills Kit through the Alexa Web Service. Then the voice command is entered and sent to the Lambda Amazon Web Service to be modeled in the JSON format. This format will be published to MQTT and MySQL Database so that it can be recognized by the system. The system will subscribe to the command as a reference for what Alexa must say. The level of accuracy and success of the system to be able to read voice command sensor data using 5 different speakers is 70%.